Forecasting of Thailand and Myanmar border trade value for strategic planning - Kasem Kunasri (2018)
© 2018 Association for Computing Machinery. Forecasting the values of border trade are needed for strategic planning, especially in the competitive enhancement strategy. This paper applies the autoregressive integrated moving average (ARIMA) models to forecast the border trade value between Thailand and Myanmar on a monthly data basis. The data used are ranged from 2007 to 2016. The results bring about the forecasting model for the further border trade investment of both countries which is useful for making the decision on part of the entrepreneurs, investors, exporters, and importers. Furthermore, the relevant agencies can use these findings to determine the promoting directions of border trade in the future.